HUBUNGAN PERAN TENAGA MEDIS, MEDIA INFORMASI DAN MOTIVASI DENGAN DETEKSI DINI KANKER PAYUDARA METODE SADARI DI PUSKESMAS DANA MULYA - Jayanti, Feri; Afrika, Eka; Rahmawati, Eka (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
Cancer is one of the leading causes of death worldwide. In 2012, cancer was the cause of death for around 8.2 million people. Lung, liver, stomach, colorectal, and breast cancers are the biggest causes of cancer deaths every year. Breast cancer is a malignant tumor that grows in the breast tissue. Every year more than 185,000 women are diagnosed with breast cancer. The purpose of this study was to determine the relationship between the role of medical personnel, exposure to information media, and motivation by conducting an early breast cancer examination using the BSE method in the region. Health Center work and Mulya. This study uses the Analytical Survey method with a cross section approach, namely the collection of data on the dependent variable and the independent variable at the same time. This research was carried out in the working area of ??the Dana Mulya Public Health Center in June-September 2021, with a sample of 40 respondents and obtained from Chi-Square test results obtained a p value of 0.004 for the role of medical personnel, a p-value of 0.046 for the variable of media information exposure, a p-value of 0.028 the motivational variable, so that it is stated that there is a relationship between exposure to media information and the implementation of early detection of breast cancer. statistics. There is a relationship between the role of medical personnel, exposure to information media and motivation simultaneously with early detection of breast cancer in the Dana Mulya Health Center Work Area.